Increasing The Learning Achievement Of Indonesian History, in Indonesia Nation Efforts Facing The Nation Disintegration through The Team Quiz Plus Method Outcomes - Gigieh Roessajanto (Metafora: Education, Social Sciences and Humanities Journal, 2021)
The purpose of this study was to determine the improvement of student learning achievement in learning Indonesian History in the material "The Efforts of the Indonesian Nation to Face National Disintegration through the Team Quiz Plus Method ". This research is a classroom action research in the X Multi Media 3 class of SMKN 12 Surabaya which was conducted in 3 cycles. Cycles 1, 2 and 3 each consist of 2 face-to-face meetings. Each cycle includes the stages of planning, action, observation, and reflection. The technique of collecting data is done by the method of observation and documentation. The instruments of data collection used are: 1) formative test questions; 2) student observation sheet. The results showed that the application of the Team Quiz Plus method proved to be able to improve student learning achievement in Indonesian History subjects in the material "The Efforts of the Indonesian Nation to Face National Disintegration".